Pilot-Based TI-ADC Mismatch Error Calibration for IR-UWB Receivers - Schmidt, Christian Andrés (2019)
In this work, we rst provide an overviewof the state of the art in mismatch error estimation and correction for time-interleaved analog to digital converters (TI-ADCs). Then, we present a novel pilot-based on-line adaptive timing mismatch error estimation approach for TI-ADCs in the context of an impulse radio ultra wideband (IR-UWB) receiver with correlation-based detection. We introduce the developed method and derive the expressions for both additive white Gaussian noise (AWGN) and Rayleigh multipath fading (RMPF) channels. We also derive a lower bound on the required ADC resolution to attain a certainestimation precision. Simulations show the effectiveness of the technique when combined with an adequate compensator. We analyze the estimation error behavior as a function of signal to noise ratio (SNR) and investigate the ADC performance before and after compensation. While all mismatches combined cause the effective number of bits (ENOB) to drop to 3 bits and to 6 bits when considering only timing mismatch, estimation and correction of these errors with the proposed technique can restore a close to ideal behavior.We also show the performance loss at the receiver in terms of bit error rate (BER) and how compensation is able to signicantly improve performance.